Reentry in a Comparative Context: Exploring Past, Present, and Future Participation in Services Between Nonurban and Urban Inmates - Ojha, Mamta U. (The prison journal, 2018)
Studies on offender reentry have consistently shown that lack of, or limited access to, needed postrelease resources and services adversely affects recidivism. Few studies have taken into consideration nonurban and urban contexts for reentry services and program participation. Toward this end, 130 currently incarcerated offenders were surveyed. The results of this study indicate that there were significant differences in employment and other services utilization observed between the two subsamples that varied depending on involvement prior to prison and during incarceration, and affecting the types of programs and services inmates would like to access postrelease.